2020
DOI: 10.3390/metabo10050199
|View full text |Cite
|
Sign up to set email alerts
|

Using Metabolomics to Identify Cell Line-Independent Indicators of Growth Inhibition for Chinese Hamster Ovary Cell-Based Bioprocesses

Abstract: Chinese hamster ovary (CHO) cells are widely used for the production of biopharmaceuticals. Efforts to improve productivity through medium design and feeding strategy optimization have focused on preventing the depletion of essential nutrients and managing the accumulation of lactate and ammonia. In addition to ammonia and lactate, many other metabolites accumulate in CHO cell cultures, although their effects remain largely unknown. Elucidating these effects has the potential to further improve the productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…engineering, [17][18][19][20] transcriptomics, 21 metabolomics, [22][23][24] and genomics. 25 Despite extensive research having been conducted on CHO cells, more research is required to further understand the biology of these cells in order to open new gateways for cell engineering.…”
Section: Cho Cells Have Been Studied In Different Research Fields Including Cellmentioning
confidence: 99%
“…engineering, [17][18][19][20] transcriptomics, 21 metabolomics, [22][23][24] and genomics. 25 Despite extensive research having been conducted on CHO cells, more research is required to further understand the biology of these cells in order to open new gateways for cell engineering.…”
Section: Cho Cells Have Been Studied In Different Research Fields Including Cellmentioning
confidence: 99%
“…Apart from contaminants, by-products from hydrolysates could also affect cell growth. A recent study has shown significant growth inhibition of the mAb-producing CHO-K1 GS-knockout and CHO-DG44 cells due to the accumulation of tryptophan in the culture (Alden et al 2020 ). In the same study, the tryptophan-derived metabolite, 5-HIAAId (5-hydroxyindolacetaldehyde), has been shown to have a detrimental effect on cell growth (Alden et al 2020 ).…”
Section: Contaminants and By-products Of Hydrolysatementioning
confidence: 99%
“…A recent study has shown significant growth inhibition of the mAb-producing CHO-K1 GS-knockout and CHO-DG44 cells due to the accumulation of tryptophan in the culture (Alden et al 2020 ). In the same study, the tryptophan-derived metabolite, 5-HIAAId (5-hydroxyindolacetaldehyde), has been shown to have a detrimental effect on cell growth (Alden et al 2020 ). This observation is further supported by a separate study investigating the effects of increased levels of tryptophan by-products and riboflavin degradant (lumichrome), both of which are detrimental to cell growth (Zang et al 2011 ).…”
Section: Contaminants and By-products Of Hydrolysatementioning
confidence: 99%
“…A challenge with such an approach is that over supplementation and consumption of certain amino acids can lead to the production of harmful byproducts. For instance, varying the amount of essential amino acid concentrations can lead to the differential regulation of amino acid metabolic pathways that could ultimately result in increased formation of harmful byproducts such as lactate or ammonia (Alden et al, 2020;Morris et al, 2020;Park, Reimonn, Agarabi, Brorson, & Yoon, 2018;Pereira, Kildegaard, & Andersen, 2018). Alternatively, supplementing amino acids in a time-dependent manner based on cell demand would ensure optimal consumption and cellular metabolism presumably resulting in better cell growth and mAb productivity.…”
Section: Introductionmentioning
confidence: 99%